Food Storage Procedures in the Kitchen of Renaissance Bali Uluwatu Resort & Spa - Muliyadi, Frederikus; Wiantara, I Gusti Nyoman; Putri , Ida Ayu Karina (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
The hotel kitchen is a critical operational area that directly affects food quality and guest safety. This study aims to analyze the food storage procedures implemented at the Kitchen of Renaissance Bali Uluwatu Resort & Spa, identify the challenges encountered in their implementation, and describe the efforts taken to overcome those challenges. The study used a qualitative descriptive approach with data collected through observation, interviews with the Executive Sous Chef, and documentation. The results show that food storage procedures have been carried out according to international hotel operational standards, including categorization by type (dry, fresh, frozen), temperature regulation, consistent application of the First In First Out (FIFO) principle, food separation to prevent cross-contamination, structured receiving processes, and routine sanitation. However, several challenges were identified: lack of staff discipline, particularly during peak hours; limited storage capacity during peak seasons; and insufficient understanding among new staff regarding food safety principles and labeling systems. Efforts to address these challenges include conducting routine briefings, implementing daily operational checklists, optimizing storage layout through re-arrangement, applying vertical storage methods, and organizing regular food safety training. This study concludes that continuous improvement of human resources, work systems, and facilities is essential to ensure food storage procedures are applied effectively and consistently.